Boycott as Resistance: The Global Movement Against Israeli-Affiliated Brands - Permana Adi Citra, Yogi; Diaz Wahyu Darmansyah, Muhammad; Ulwan Fadhlurrahman, Fauzan (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
The ongoing Israeli-Palestinian conflict has provoked widespread global reactions, particularly in the form of economic resistance through consumer boycotts. These boycotts target Israeli-affiliated brands and multinational corporations perceived to be complicit in the occupation and oppression of Palestinians. The core issue lies in the ethical concerns of corporate involvement in human rights violations and the extent to which consumers can influence political dynamics through economic actions. This study aims to explore the global boycott movement as a form of nonviolent resistance, with a specific focus on the Boycott, Divestment, Sanctions (BDS) campaign. Utilizing a library research methodology, this paper draws upon academic literature, news reports, campaign materials, and corporate statements to analyze the motivations, strategies, and impacts of boycott actions worldwide. It investigates how consumer behavior intersects with political activism, and how the digital age amplifies such movements. The research finds that boycotts serve not only as an expression of solidarity with oppressed populations but also as a tool to pressure companies and governments to reevaluate their stances and affiliations. Although the economic impact varies, the symbolic power of collective consumer action contributes significantly to shaping public discourse on global justice. This study highlights the growing importance of ethical consumerism in international relations and recommends further investigation into the legal, economic, and diplomatic consequences of sustained boycott movements.